Respostas

2013-12-10T23:14:02-02:00
X(x+5) = x² + 5x
x² + 5x = 2x + 28
x² + 3x - 28 = 0
S: -3
P: -28

r: 4 e -7

Creio que é assim!
1 4 1
mt obrigada ^_^
cê entendeu o que eu fiz? o lance da soma e do produto?
ss *-*
A melhor resposta!
2013-12-10T23:14:34-02:00
X(x+5)=2x+28
x²+5x=2x+28
x²+5x-2x=28
x²+3x-28=0

Aplicamos a fórmula de Bhaskara:

Δ = b² -4ac
Δ = 3² -4 *1 * (-28)
Δ = 9 + 112
Δ = 121
x' = (-b + √∆)/ 2a
(-3 + 11)/2 * 1
(-3 + 11)/2
8/2= 4
x'' = (-b - √∆)/ 2a
(-3 - 11)/2 * 1
(-3 - 11)/2
-14/2= -7

S = { 4,-7}
2 5 2